2019
DOI: 10.1016/j.jds.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of cone beam computed tomography in measuring thicknesses of hard-tissue-mimicking material adjacent to different implant thread surfaces

Abstract: Background/purpose To evaluate the measurement accuracy of hard-tissue thicknesses adjacent to dental implants with different thread designs on images obtained from cone beam computed tomography (CBCT) using an in vitro model. Materials and methods On 4 × 13-mm implant, the neck of the implant was designed with micro-threads, and the apical part was covered by macro-threads; these implants were placed in a vinyl polysiloxane block that mimicke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Finding an accurate yet non‐invasive method to assess implant buccal bone has been challenging. Direct clinical assessment that involves flap reflection is invasive whereas radiographic CBCT assessment has its limitations (Benic et al, 2013; González‐Martín et al, 2016; Pelekos et al, 2018; Tyndall et al, 2012) where thin facial alveolar bone shows less accurately in CBCT than reality (González‐Martín et al, 2016; Razavi et al, 2010; Vanderstuyft et al, 2019; Yen et al, 2019) found that about 60% of the cases buccal bone was not visible.…”
Section: Introductionmentioning
confidence: 99%
“…Finding an accurate yet non‐invasive method to assess implant buccal bone has been challenging. Direct clinical assessment that involves flap reflection is invasive whereas radiographic CBCT assessment has its limitations (Benic et al, 2013; González‐Martín et al, 2016; Pelekos et al, 2018; Tyndall et al, 2012) where thin facial alveolar bone shows less accurately in CBCT than reality (González‐Martín et al, 2016; Razavi et al, 2010; Vanderstuyft et al, 2019; Yen et al, 2019) found that about 60% of the cases buccal bone was not visible.…”
Section: Introductionmentioning
confidence: 99%
“…Radiographic CBCT assessment is less invasive but has its limitations in terms of accuracy, especially concerning detecting thin facial bone. Buccal bone is less accurately exhibited in CBCT, underestimating thin bone dimension, further complicating assessment 15–21 . To eliminate the shortcomings of the CBCT, the buccal bone changes measuring device introduced by 22 have proven itself to be more accurate and less invasive 23–25 …”
Section: Introductionmentioning
confidence: 99%
“…Buccal bone is less accurately exhibited in CBCT, underestimating thin bone dimension, further complicating assessment. [15][16][17][18][19][20][21] To eliminate the shortcomings of the CBCT, the buccal bone changes measuring device introduced by 22 have proven itself to be more accurate and less invasive. [23][24][25] Accordingly, this prospective clinical trial was designed to examine the effect of labial bone thickness on the buccal bone resorption in immediate implants and assess the accuracy of buccal bone measurement methods using two different techniques.…”
Section: Introductionmentioning
confidence: 99%
“…For the first time, cotton threads formed a microfluidic system that was used to conduct a fast and simple Turkevich synthesis of gold nanoparticles (AuNPs) using minute amounts of chemicals. Yen et al [4] studied and examined the topic that Cone beam computed tomography accuracy in determining the thickness of hardtissue-mimicking material close to various implant thread surfaces. Using an in vitro model, assess the measuring accuracy of hard-tissue thicknesses close to dental implants using various thread patterns on images generated from cone beam computed tomography (CBCT).…”
Section: Introductionmentioning
confidence: 99%